2002
DOI: 10.1063/1.1453954
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the reaction mechanism of CO2 with Ti atom in the ground and excited electronic states

Abstract: Articles you may be interested inKinetic and dynamic studies of the Cl(2 P u) + H2O( X ̃ 1 A 1) → HCl( X ̃ 1Σ+) + OH( X ̃ 2Π) reaction on an ab initio based full-dimensional global potential energy surface of the ground electronic state of ClH2O J. Chem. Phys. 139, 074302 (2013); 10.1063/1.4817967 Time-dependent quantum wave packet study of the Ar+H2 +→ArH++H reaction on a new ab initio potential energy surface for the ground electronic state (12 A′) J. Chem. Phys. 138, 174305 (2013); 10.1063/1.4803116 Accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…In the case of titanium–CO 2 interaction, C–O bond breaking occurs readily, and the required energy can easily be supplied in the ion source, even by mere condensation of CO 2 onto the metal atom. These results are reminiscent of the observed bond insertion processes that occur for neutral Ti atoms. ,, Because of the high oxophilicity of titanium, the metal–oxygen bond formed upon bond insertion (forming the metal–oxo ligand) is stronger than the same bond formed for other metals. The calculated Mulliken–Mayer bond orders for the M–O bond in each case are as follows: Ti, 2.11; Fe, 1.52; Ni, 1.29, following the oxophilicity trend of Ti > Fe > Ni .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In the case of titanium–CO 2 interaction, C–O bond breaking occurs readily, and the required energy can easily be supplied in the ion source, even by mere condensation of CO 2 onto the metal atom. These results are reminiscent of the observed bond insertion processes that occur for neutral Ti atoms. ,, Because of the high oxophilicity of titanium, the metal–oxygen bond formed upon bond insertion (forming the metal–oxo ligand) is stronger than the same bond formed for other metals. The calculated Mulliken–Mayer bond orders for the M–O bond in each case are as follows: Ti, 2.11; Fe, 1.52; Ni, 1.29, following the oxophilicity trend of Ti > Fe > Ni .…”
Section: Resultsmentioning
confidence: 72%
“…As an example of more extreme undercoordination, the interaction of CO 2 with bare, atomic Ti and molecular TiO x ( x = 1–2) has been studied in experimental and computational work on gas-phase and matrix-isolated titanium and titanium oxide neutrals and cations, investigating the structure of CO 2 -single metal atom complexes and the activation that occurs. Notably, this work showed that insertion of Ti into C–O bonds occurs for neutral Ti and TiO reactions with CO 2 , , as well as for Ti + with CO 2 . , In fact, Mascetti and co-workers demonstrated that a Ti atom spontaneously inserts into CO 2 with no barrier, forming a strong TiO bond and a metal carbonyl. , Early transition metals, with their high oxophilicities, are generally likely to form insertion products in interaction with CO 2 , due to the strength of the formed metal–oxygen bond . Other works have shown CO bond insertions in cationic clusters of CO 2 with titanium and vanadium, as well as silicon and nickel. …”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanisms relevant for reduction of CO 2 to CO mediated by a single anionic metal center, M – , are illustrated in Figure , and the corresponding computed [MP2/def2-TZVPPD] energies are presented in Table . The fully metal inserted complex OMCO – is reported as a key intermediate for the early transition metals ,, but turned out not to correspond to a stable minimum energy structure for any of the metal anions studied here. Consequently, we will only need to consider [M,CO 2 ] − intermediates with intact CO 2 cores, consistent with previously published literature on reactions between these metals and CO 2 . ,, …”
Section: Resultsmentioning
confidence: 71%
“…It is well established that metal atoms and anions may add CO 2 to form complexes in gas phase reactions, formally metal carbonites (MCO 2 ). Their preferred structures are shown in Scheme , which in the case of alkali and alkaline earth metals is the bidentate coordination of the metal to both oxygen atoms (κ 2 -O 2 C), while for transition metals, the metal typically binds to the carbon atom (η 1 -CO 2 ) or in a side-on fashion (η 2 -CO 2 ). Early transition metals, M = Sc, Ti, V, and Cr, ,, even insert into one of the C–O bonds with subsequent CO elimination: …”
Section: Introductionmentioning
confidence: 99%
“…Ti(CO 2 ) complexes in various coordination modes were located on the triplet and quintet potential surfaces; the triplet state (O,O) coordination mode is the most stable one, but it lies above the OTiCO molecule by about 125 kJ mol −1 . Later, Mebel et al 50 made a very detailed study of the same reactions and came to the conclusion that the most energetically favorable reaction mechanism was the insertion of the Ti atom into a C-O bond via an η 2 (C,O)-coordinated Ti(CO 2 ) complex, to produce the triplet OTi(CO) molecule. A comparison of reaction mechanisms for alkaline-earth and early transition metal atoms indicates that, although all of them can enhance CO 2 re-forming into CO, the early transition metal atoms (Sc, Ti, V) are the best ones for this purpose.…”
Section: Reactions In Low-temperature Matrixesmentioning
confidence: 99%